Performance evaluation of a scaled-up membraneless organic-based hybrid flow battery - Yu, Feilin; Zhao, Wenbo; Leung, Puiki; Mohd Rusllim, Mohamed; Wei, Lei; Shah, Akeel A.; Liao, Qiang (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
This article presents an evaluation of the performance of a membrane-less organic-based flow battery using low-cost active materials, zinc and benzoquinone, which was scaled up to 1600 cm2, resulting in one of the largest of its type reported in the literature. The charge–discharge cycling of the battery was compared at different sizes and current densities, and its performance was evaluated under various mass transport and operating conditions. The results showed that the round-trip coulombic and voltage efficiencies were over 90% and 85%, respectively, for the laboratory-scale (1 cm2 electrode) cell, but these performances tended to deteriorate with the scaled-up (1600 cm2 electrode) cell due to inadequate mass transfer and sediment coverage of quinone, as well as the formation of a passivation film on the zinc anode. Despite this, the scaled-up batteries exhibited high coulombic and voltage efficiencies of up to 99% and 68.5%, respectively, at a current density of 10 mA cm−2. The capital cost of this system is also estimated to be several times lower than those of commercially available all-vanadium flow batteries and zinc bromide flow batteries for demand charge management applications.